What influence Muslims to make wills?: insights into its determinants - Abd. Wahab, Norazlina; Hashim, Suraiya; Abd Ghani, Nur Amalina (Universiti Sains Islam Malaysia, 2019)
The aim of this study is to investigate factors that influence the practice of making will among Muslims in Malaysia. In Malaysia, it can be noted that some progress towards enhancing Islamic estate planning has taken place, particularly in the practice of Islamic will. Islamic estate planning industry in Malaysia has grown and now offers a variety kind of products to facilitate Malaysian Muslims to manage and improve their estate planning matters. Nevertheless, the value of unclaimed and frozen assets in this country keeps growing annually. Hence, this study aims to look at the practice of making wills in Malaysia and investigate factors that influence Muslims to do it. Using a quantitative analysis, a total of 338 questionnaires were used to achieve the objective. The method of analysis employed in this study include Independent Sample T-Test, One-Way Analysis of Variance (ANOVA), Pearson and Correlation as well as Multiple Regression. The results of this study indicate that there is a significant difference between gender (male and female), educational levels and monthly income levels towards Islamic will practice. Nevertheless, only ethnicity showed no significant difference towards Islamic will practice. The correlation analysis showed a significant and positive correlation between knowledge, wealth management,institutional factor and religiosity toward Islamic will practice. The results show that knowledge and wealth management are the main variables that influence Muslims towards Islamic will practice. This explains that higher level of knowledge and wealth management among Muslims will lead to a higher practice of Islamic will. These results suggest that the government and Islamic estate planning industry should put a greater emphasis on attracting and educate Muslims to manage and plan their wealth well during their lifetime.